2021
DOI: 10.1039/d0an02193h
|View full text |Cite
|
Sign up to set email alerts
|

In situ detection of plasma exosomal microRNA for lung cancer diagnosis using duplex-specific nuclease and MoS2 nanosheets

Abstract: An in situ detection of plasma exosomal microRNA for lung cancer diagnosis using duplex-specific nuclease and molybdenum disulfide nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Generally, MoS 2 nanosheets are dynamic quenchers, which can interact with excited molecules and cause the fluorescence decrease of sensors. 13 Previous studies found that MoS 2 could be modified with FAM-labeled aflatoxin M 1 (FAM-CS) aptamers, and the fluorescence of the sensors was extinguished due to the resonance energy transfer between MoS 2 and FAM-CS. With the increase of aflatoxin M 1 (AFM 1 ) concentration, the FAM detached from MoS 2 nanosheets and created an AFM 1 -FAM-CS ternary structure with AFM 1 , resulting in the enhancement of fluorescent intensity.…”
Section: Bottom-up Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, MoS 2 nanosheets are dynamic quenchers, which can interact with excited molecules and cause the fluorescence decrease of sensors. 13 Previous studies found that MoS 2 could be modified with FAM-labeled aflatoxin M 1 (FAM-CS) aptamers, and the fluorescence of the sensors was extinguished due to the resonance energy transfer between MoS 2 and FAM-CS. With the increase of aflatoxin M 1 (AFM 1 ) concentration, the FAM detached from MoS 2 nanosheets and created an AFM 1 -FAM-CS ternary structure with AFM 1 , resulting in the enhancement of fluorescent intensity.…”
Section: Bottom-up Approachesmentioning
confidence: 99%
“…12 Furthermore, MoS 2 -based materials possess superior structures featuring high specific surface area, multiple catalytic sites, and excellent migration capability, allowing in situ degradation of the aforementioned agricultural contaminants in agricultural water or soil. 13 Despite MoS 2 having been extensively investigated as a multifunction toolkit for agricultural contaminant control recently, a comprehensive review is lacking in this respect. In this regard, this has spurred our enormous interest to summarize the MoS 2 -based platform for agricultural contaminant control, and this review is anticipated to provide certain guidance for emerging agricultural contaminant control techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, miRNAs are mainly detected by end-point technologies, including northern blotting, qualitative reverse transcription-polymerase chain reaction (qRT-PCR) [ 51 ], Northern blotting [ 52 ], and microarrays [ 53 ], which require a good deal of samples simultaneously take a long time. MoS 2 nanomaterial-based fluorescent biosensors can overcome the above defects and improve detection sensitivity and specificity [ 54 , 55 ]. Xiao et al [ 56 ] found that polycytosine (polyC) DNA could non-covalently functionalize MoS 2 nanosheets to retain DNA activity and increase the recognition ability of probes.…”
Section: Biosensorsmentioning
confidence: 99%
“…The levels of serum miRNA-200b-5p, miRNA-378, miRNA-502-5p, miRNA-629, miRNA-17 and miRNA-100 are remarkably higher in individuals with lung adenocarcinoma compared with pulmonary granuloma cases as well as healthy smokers [ 67 ]. High miRNA-21 and miRNA-155 amounts in lung cancer exosomes have been considered potential biomarkers for diagnosing lung cancer [ 68 , 69 ]. The levels of miRNAs, including miRNA-205, miRNA-19a, miRNA-19b, miRNA-30b and miRNA-20a, were shown to be significantly decreased after operation [ 70 ].…”
Section: Expression Of Exosomal Mirnas In Cancersmentioning
confidence: 99%